2010
DOI: 10.1002/ejoc.201000305
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐Closing of 1,7‐ and 1,8‐Enynes of Propargylic O,O‐Acetals by Ruthenium‐Catalysed Intramolecular Metathesis

Abstract: Acyclic 1,7-and 1,8-enynes with the alkyne moiety directly connected to the asymmetric carbon of an ethyl acetal have been obtained in two steps from the corresponding aldehydes. Ring-closing metathesis of these enynes delivered the corresponding six-and seven-membered cyclic 1,3-dienes in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The following known compounds were isolated as pure samples and showed data matching those of reported compounds: (S)-2, [16] 3, [15] (Ϯ)-7b, [19a] 8a and 8b, [14] 9b. [31] General Procedure for ZnBr 2 -Catalyzed Diels-Alder Reactions: To a solution of freshly prepared sulfinylquinone (S)-2 (0.75-1.00 mmol, 1 equiv.)…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…The following known compounds were isolated as pure samples and showed data matching those of reported compounds: (S)-2, [16] 3, [15] (Ϯ)-7b, [19a] 8a and 8b, [14] 9b. [31] General Procedure for ZnBr 2 -Catalyzed Diels-Alder Reactions: To a solution of freshly prepared sulfinylquinone (S)-2 (0.75-1.00 mmol, 1 equiv.)…”
Section: Methodsmentioning
confidence: 88%
“…[21] RCEM reactions leading to dienes 7a-d were performed using Grubbs 1st generation catalyst (1 mol-%), however, these conditions were totally ineffective for the RCEM of the precursors of 8a, 8b, 9a, and 9b. Finally, seven-membered ring based dienes 8a and 8b were obtained in good yields (80 and 70 %, respectively), [14] as well as the corresponding five-membered rings 9a and 9b (72 and 68 %, respectively) by reaction with Grubbs 2nd generation catalyst (5 mol-%) in dichloroethane under an ethylene atmosphere at 80°C. Returning to our model reaction (Scheme 2), we observed that cycloadduct 6 was stable at -20°C for several months (even years) and that it was possible to perform a desulfinylation using Raney-Ni in cold MeOH (-20°C) to give the corresponding cis-decalin 10 in 70 % yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohols 4a , b , e – l were prepared according to literature procedure . These compounds have been previously described in the literature: 1-(furan-3-yl)-2-methylpropan-1-ol ( 4a ), 1-(furan-3-yl)­pentan-1-ol ( 4b ), 1-(furan-3-yl)-2,2-dimethylpropan-1-ol ( 4e ), furan-3-yl­(phenyl)­methanol ( 4f ), , 1-(furan-3-yl)-2-phenylethanol ( 4g ), 1-(furan-3-yl)­ethanol ( 4h ), 1-(furan-3-yl)­but-3-en-1-ol ( 4i ), 1-(furan-3-yl)­pent-4-en-1-ol (11j) , 1-(furan-3-yl)­prop-2-en-1-ol ( 11k ), , 1-(furan-3-yl)­but-3-yn-1-ol ( 11l ) …”
Section: Methodsmentioning
confidence: 99%
“…49 (62 mg 78%) clear oil 1 1-Phenyl-3-buten-1-ol (5). 51 (Eluent: 10:1 hexane/ethyl acetate, 72 mg 67%) clear oil 1 (Z)-(2-Methoxyethenyl)benzene (6). 52 (Eluent: 10:1 hexane/ethyl acetate, 61 mg 62%) clear oil 1…”
Section: ■ Conclusionmentioning
confidence: 99%